1997
DOI: 10.1143/jjap.36.l583
|View full text |Cite
|
Sign up to set email alerts
|

Current-Voltage Characteristics of Field Electron Emission through Phthalocyanine Molecules on a Tungsten Field Emitter

Abstract: The current-voltage characteristics on field emission through a four-leaf pattern, a two-leaf pattern and a single large bright spot of adsorbed Cu- and Co-phthalocyanines on a tungsten tip have been measured, and Fowler-Nordheim (FN) plots of field emission were obtained. The slopes of the FN plots for the four-leaf patterns were almost equal to or even a little higher than those for the substrate surface. In contrast, the slopes of the two-leaf patterns were about 10–15% lower than those of the substrate sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Other experiments have already indicated that the emission from CuPc arises from multiple states 26,27 and that the different image types can be associated with different Fowler-Nordheim slopes. 28 In the course of our experiments, a single tantalizing run of data was acquired in which a FEEM quadruplet with a doublet barrier map spontaneously converted to a FEEM doublet with the same orientation as the barrier map doublet as the field strength was increased. Unfortunately, insufficient data were acquired to construct a barrier map for this subsequent FEEM doublet and the effect has proven difficult to reproduce.…”
Section: Discussionmentioning
confidence: 99%
“…Other experiments have already indicated that the emission from CuPc arises from multiple states 26,27 and that the different image types can be associated with different Fowler-Nordheim slopes. 28 In the course of our experiments, a single tantalizing run of data was acquired in which a FEEM quadruplet with a doublet barrier map spontaneously converted to a FEEM doublet with the same orientation as the barrier map doublet as the field strength was increased. Unfortunately, insufficient data were acquired to construct a barrier map for this subsequent FEEM doublet and the effect has proven difficult to reproduce.…”
Section: Discussionmentioning
confidence: 99%
“…Emitters require a low effective work function, high geometrical aspect ratio, and good thermal and chemical stability 5 6 7 . A variety of one-dimensional (1D) nanomaterials have been studied as novel emitters, including 1D carbon nanomaterials 8 9 10 11 , 1D nano-metal oxide 12 13 14 15 , and 1D nano-metal materials 12 16 17 18 . However, from a practical point of view, the in situ growth of emitters at low temperature (<450 °C) on a desired substrate or the production of emitters in powder form are required for industrial applications.…”
mentioning
confidence: 99%